The Relationship between Knowledge Level of Foot Care and Prevention of Diabetic Foot Ulcers in Diabetes Mellitus Patients at the Lok Bahu Community Health Center Samarinda - Simarmata, Pratiwi Christa; Ahmad, Erwan; Octora, Debi Dinha; Wati, Syatria; Hayati, Kardina (Fakultas Kedokteran, 2026)
Introduction: Diabetes mellitus is a chronic disease that can cause various complications, one of which is diabetic foot ulcers. This complication can be prevented through proper foot care, but the success of prevention is greatly influenced by the patient's level of knowledge. Good knowledge allows patients to understand the risks, recognize early signs of wounds, and take preventive measures independently. This study aims to determine the relationship between the level of foot care knowledge and the prevention of diabetic foot ulcers in diabetes mellitus patients at the Lok Bahu Community Health Center in Samarinda. Methods: This study used a quantitative design with a cross-sectional approach with 70 respondents of diabetes mellitus patients selected through a purposive sampling technique. Data were collected using a questionnaire regarding the level of foot care knowledge and diabetic foot ulcer prevention behavior. Analysis used the Chi-Square test with a significance level of 0.05. Results: The results showed that most respondents had a good level of foot care knowledge as many as 44 respondents (62.9%) and a good level of diabetic foot ulcer prevention behavior as many as 60 respondents (85.7%). The statistical test results showed a p-value of 0.045, indicating a significant relationship between the level of foot care knowledge and the prevention of diabetic foot ulcers. Conclusion: The level of foot care knowledge is significantly related to the prevention of diabetic foot ulcers in patients with diabetes mellitus. Structured, ongoing, and applicable foot care education is needed to improve patients' ability to perform prevention independently.